Laser‐activated transforming growth factor‐β1 induces human β‐defensin 2: implications for laser therapies for periodontitis and peri‐implantitis - Tang, E.; Khan, I.; Andreana, S.; Arany, P. R. (Journal of periodontal research, 2017)
Background There is increasing popularity of high‐power lasers for surgical debridement and antimicrobial therapy in the management of peri‐implantitis and periodontal therapy. Removal of the noxious foci would naturally promote tissue healing directly. However, there are also anecdotal reports of better healing around routine high‐power laser procedures. The precise mechanisms mediating these effects remain to be fully elucidated. This work examines these low‐dose laser bystander effects on oral human epithelial and fibroblasts, particularly focusing on the role of human β‐defensin 2 (HBD‐2 or DEFB4A), a potent factor capable of antimicrobial effects and promoting wound healing. Material and Methods Laser treatments were performed using a near‐infrared laser (810 nm diode) at low doses. Normal human oral keratinocytes and fibroblast cells were used and HBD‐2 mRNA and protein expression was assessed with real time polymerase chain reaction, western blotting and immunostaining. Role of transforming growth factor (TGF)‐β1 signaling in this process was dissected using pathway‐specific small molecule inhibitors. Results We observed laser treatments robustly induced HBD‐2 expression in an oral fibroblast cell line compared to a keratinocyte cell line. Low‐dose laser treatments results in activation of the TGF‐β1 pathway that mediated HBD‐2 expression. The two arms of TGF‐β1 signaling, Smad and non‐Smad are involved in laser‐mediated HBD‐2 expression. Conclusions Laser‐activated TGF‐β1 signaling and induced expression of HBD‐2, both of which are individually capable of promoting healing in tissues adjacent to high‐power surgical laser applications. Moreover, the use of low‐dose laser therapy itself can provide additional therapeutic benefits for effective clinical management of periodontal or peri‐implant disease.